The moderating effect of switching cost on the influence of social influence and price towards switching intention - Muhammad Fauzan; Yunita Engriani (Marketing Management Studies, 2021)
The purpose of this study to analyse: (1) The effect of social influence on switching intention’s online shop Tokopedia in Padang City, (2) The effect of price on switching intention’s online shop Tokopedia in Padang City, (3) The effect of Switching cost moderating social influence on switching intention’s online shop Tokopedia in Padang City, (4) The effect of Switching cost moderating price on switching intention’s online shop Tokopedia in Padang City. The population in this study were all Padang City’s residence, while the number of samples in this study was determined by the non- probability sampling method and the technique used was purposive sampling to obtain a sample of 100 samples. The analysis technique used is Structural Equation Modeling (SEM) analysis using Smart PLS Software 3. The result of this study indicates: Social influence and price has a significant and positive effect on switching intention’s online shop Tokopedia in Padang City. Switching cost has a negative and not significant effect to moderating social influence on switching intention’s online shop Tokopedia in Padang City. (4) Switching cost has a negative and not significant effect to moderating price on switching intention’s online shop Tokopedia in Padang City.